2022
DOI: 10.1002/eom2.12191
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale fabrication of core‐shell triboelectric braided fibers and power textiles for energy harvesting and plantar pressure monitoring

Abstract: Flexible and wearable energy harvesting devices and multifunctional sensors have been widely reported, but challenges in the large‐scale manufacturing process still exist. This work reports a large‐scale fabrication method of core‐shell triboelectric braided fibers that exhibit stable structure and strong tensile strength, which can be further integrated into power textiles with different fabric structures, such as weaving and knitting, with the purpose of biomechanical energy harvesting or plantar pressure mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 39 publications
0
41
0
Order By: Relevance
“…Through high-speed ring spinning technology, ≈2,000 m of NPRY can be prepared in just 1 h. In order to overcome the shortcomings of complex preparation process and the inability to continuously produce, Li et al used a braiding machine to weave PVDF on the surface of silver-coated nylon fibers to make F-TENG with a core-shell structure (Figure 4b). [52] Yang et al prepared F-TENG by combining core-spun spinning method and surface coating method, [53] as displayed in Figure 4c. First, a conductive corespun yarn is produced using a core-spinning method.…”
Section: Spinningmentioning
confidence: 99%
“…Through high-speed ring spinning technology, ≈2,000 m of NPRY can be prepared in just 1 h. In order to overcome the shortcomings of complex preparation process and the inability to continuously produce, Li et al used a braiding machine to weave PVDF on the surface of silver-coated nylon fibers to make F-TENG with a core-shell structure (Figure 4b). [52] Yang et al prepared F-TENG by combining core-spun spinning method and surface coating method, [53] as displayed in Figure 4c. First, a conductive corespun yarn is produced using a core-spinning method.…”
Section: Spinningmentioning
confidence: 99%
“…Output electrical energy can light up 116 LEDs simultaneously and can be used as a plantar pressure sensor (Fig. 3f ) [ 50 ]. Frictional movements between the arm and the axilla can also be collected by a wearable TENG.…”
Section: Tengs As Wearable Power Sourcesmentioning
confidence: 99%
“…Copyright 2021, American Chemical Society; Copyright 2021, Elsevier. (e and f) Elbow [ 49 , 50 ]. Copyright 2019, Springer Nature; Copyright 2022, WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.…”
Section: Tengs As Wearable Power Sourcesmentioning
confidence: 99%
“…The related study was recently presented. For example, Dong et al reported a large-scale prepared core-shell type knitting triboelectric fiber [ 46 ]. As depicted in Figure 4 c, silver-coated nylon yarns were chosen as the electrode for its good flexibility, stitchability and excellent conductivity.…”
Section: Fabric/fiber-based Triboelectric Layers In Tengsmentioning
confidence: 99%